Prediction of in-hospital mortality in patients aged 75 years and older with acute ST-segment elevation myocardial infarction using logistic regression and classification tree - K. G. Pereverzeva; S. S. Yakushin (Кардиоваскулярная терапия и профилактика)
Aim. To study risk factors for in-hospital mortality in patients with acute myocardial infarction (MI) with ST-segment elevation (STEMI) aged ≥75 years.Material and methods. This retrospective analysis analyzed medical records of 174 patients aged ≥75 years hospitalized at the regional cardiology clinic due to STEMI in 2020-2021. There were 52 (29,9%) men. The median age for all patients was 81 [79; 85] year.Results. Inhospital mortality was 24,1%. Binary logistic regression revealed the following factors increasing the risk of inhospital mortality: cardiogenic shock (CS) — odds ratio (OR) 39,04; 95% confidence interval (CI): 8,87-171,74 (p<0,001); ventricular tachycardia (VT) — OR=60,52; 95% CI: 5,21-703,45 (p=0,001); white blood cell (WBC) count — for each increase by 1×109/l — OR=1,15; 95% CI: 1,05-1,26 (p=0,002). At the same time, history of heart failure (CHF) reduced the death risk (OR=0,04; 95% CI: 0,009-0,21 (p<0,001)). Classification tree found that 100% mortality was predicted in patients with CS and without diabetes and a history of MI and in patients with pulmonary edema and without CS, VT and HF. Mortality of 83,3% was predicted in patients without CS and without VT with a history of HF, WBC count ≥14,5×109/L and body mass index ≤23,7 kg/m2. In addition, mortality of 75,0% was predicted in patients without CS, but with VT, as well as in patients with CS without diabetes and with a history of MI. In patients with CABG and diabetes, the predicted mortality rate was 50,0%.Conclusion. The strongest factors associated with the risk of inhospital death were CS, VT, and high WBC count. The positive effect on the prognosis of pre-existing diseases, in particular HF, is apparently associated with the protective effect of previously taken therapy. This assumption needs to be confirmed based on prospective studies.